(untitled) (Atti del Sodalizio Glottologico Milanese, 2013)
The purpose of this article is to review briefly some new and, according to us, significant proposals of signs transliteration of Linear A sillabary following homography: homophony criterion whith Linear B signs according to TMT principles, referring in particular to the possible phonetic values of signs pertaining to both writings but still not transliterated in Linear B, and verifying the results of the application of Linear A occurrences. KEYWORDS: Linear A, Linear B, writing systems, transliteration, homography